The effectiveness of agricultural extension in rice farming in Bantaeng Regency, Indonesia: Employing structural equation modeling in search for the effective ways in educating farmers - Salam, Muslim; Jamil, Muhammad Hatta; Tenriawaru, A. Nixia; Kamarulzaman, Nitty Hirawaty; Syam, Siti Hardiyanti; Rahmadanih, .; Ramadhani, Anggun; Bidangan, Anny Melody; Muslim, Ahmad Imam; Bakheet Ali, Hamed Noralla; Ridwan, Muhammad (Elsevier, 2024)
The research's objective was to examine the factors that directly and indirectly influence the effectiveness of agricultural extension in rice farming in Bantaeng Regency, Indonesia. The sample size included 155 rice farmers, and the Structural Equation Modeling (SEM) was used to examine the rice farmer data. The results indicated that latent variables such as farmer engagement (FER), family resources (FRR), application of product inputs (APR) (β = 3.383), and crop management (CMR, β = −2.712)) all have a significant effect on the effectiveness of agricultural extension (EAR). The findings of this study explained that the FER (β = 0.244), together with the FRR (β = 0.923), exerted a significant influence on the APR, potentially increasing rice production. Meanwhile, the APR (β = 0.777) provided good results on the CMR and EAR. The indirect effect hypothesis shows that the APR and CMR mediated the relationship between FER (β = 0.203), FRR (β = 3.383), and EAR, which emphasizes the importance of APR and CMR. Therefore, in improving the EAR programs, it is recommended that extension agencies and local governments provide support to rice farmers in their participation in agricultural organizations. This support should empower rice farming families, ensure proper allocation of agricultural inputs, and effectively manage rice crops using sustainable management principles. As a result of the findings of this study, individuals responsible for designing and managing agricultural extension programs will also gain important insights and data from the real world. Furthermore, as a consequence, agricultural extension agencies can continue to educate farmers and improve rice farming methods.